Development of Audio-Visual Media Based on Video Tutorials to Support Digital Literacy in Practicum Activities - Amizera, Susy; Destiansari, Elvira; Oktavia, Nur (FKIP Universitas Lampung, 2023)
Abstract: Video tutorials are audio-visual media that can guide practicum activities. Videos can facilitate digital literacy skills, supporting students' skills in using digital technology to access and communicate in practicum activities. The research aims to develop audio-visual media based on video tutorials to support students' digital literacy skills in practicum activities. The type of research is Research and Development (R&D) research using the Borg & Gall model. Data collection techniques include administering questionnaires and pre-post tests. Data analysis used a Likert scale and n-gain test. The research results show that the product was developed during water pollution activities. Validation results with very good interpretation. Student responses to video tutorials can provide an overview of students' digital literacy abilities accompanied by high n-gain values for each indicator. Thus, developing audio-visual media based on video tutorials can strategically support students' digital literacy skills in practicum activities. Keywords: audio-visual media, video tutorials, practicum activities, digital literacy. Abstrak: Video tutorial merupakan media audio-visual yang dapat menjadi penuntun kegiatan praktikum. Penggunaan video dapat memfasilitasi kemampuan literasi digital yang dapat mendukung keterampilan mahasiswa dalam penggunaan teknologi digital untuk mengakses dan berkomunikasi dalam kegiatan praktikum. Tujuan penelitian yaitu mengembangan media audio-visual berbasis video tutorial untuk menunjang kemampuan literasi digital mahasiswa pada kegiatan praktikum. Jenis penelitian yaitu penelitian Research and Development (R&D) menggunakan model Borg & Gall. Teknik pengumpulan data berupa pemberian angket dan tes awal-akhir. Analisis data dilakukan dengan menggunakan skala likert dan n-gain test. Hasil penelitian menunjukkan bahwa produk dikembangkan pada kegiatan praktikum pencemaran air. Hasil validasi dengan interpretasi sangat baik. Respon mahasiswa pada video tutorial dapat memberikan gambaran tentang kemampuan literasi digital mahasiswa disertai nilai n-gain tinggi pada tiap indikator. Dengan demikian Pengembangan media audio-visual berbasis video tutorial dapat dijadikan sebagai langkah strategis dalam mendukung kemampuan literasi digital mahasiswa pada kegiatan praktikum. Kata kunci: media audio-visual, video tutorial, kegiatan praktikum, literasi digital. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp901-911